2012
DOI: 10.5402/2012/485720
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Positive Status Disclosure and Associated Factors among Children in North Gondar, Northwest Ethiopia

Abstract: Introduction. Clinical reports have indicated positive outcomes associated with disclosure of HIV-positive status in children. This study assessed the level and associated factors of HIV-positive status disclosure to HIV-infected children in northwest Ethiopia. Methods. Institution-based cross-sectional study was conducted among HIV-positive children from March to April 2012. Data were collected using a structured questionnaire by face-to-face interview technique. Bivariate and multivariate analyses were perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
52
6
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(76 citation statements)
references
References 16 publications
9
52
6
2
Order By: Relevance
“…Although the frequency of ALHIV fully disclosed of their HIV-serostatus varies according to studies in Africa, it remains overall low ranging from 16% to 39% [36][37][38][39][40][41]. In our study, we found that only 46.1% knew their HIV status at baseline, and 74.2% by 24 months of follow-up.…”
Section: Discussioncontrasting
confidence: 60%
“…Although the frequency of ALHIV fully disclosed of their HIV-serostatus varies according to studies in Africa, it remains overall low ranging from 16% to 39% [36][37][38][39][40][41]. In our study, we found that only 46.1% knew their HIV status at baseline, and 74.2% by 24 months of follow-up.…”
Section: Discussioncontrasting
confidence: 60%
“…Although the frequency of ALHIV fully disclosed of their HIV-serostatus varies according to studies in Africa, it remains overall low ranging from 16% to 39% [36][37][38][39][40][41]. In our study, we found that only 46.1% knew their HIV status at baseline, and 74.1% by 24 months of follow-up.…”
Section: Discussioncontrasting
confidence: 60%
“…In our study only nine out of 99 children were younger than 6 years when they were told their diagnosis. Caregivers delay disclosure till older age because they believe that at early age, the child does not have the maturity needed to understand the disease [10,24,25].…”
Section: Discussionmentioning
confidence: 99%